IDENTIFIKASI CACING TANAH DI TEMPAT PEMBUANGAN AKHIR (TPA) MUARA FAJAR UNTUK RANCANGAN LKPD ELEKTRONIK BIOLOGI DI SMA - Meliana, Meliana; Suwondo, Suwondo; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Absract: This study aims to identify the types of earthworms and their potential to produce electronic LKPD designs on the concept oligochaetes in class X even semester KD 3.9 and 4.9. This research was carried out from August to September 2021 at Muara Fajar landfills and Laboratory of the Biology Education Study Program. This research consist of two stages, namely the research phase I is a descriptive study with a survey method to identify the types of earthworm. Earthworm sampling was carried out using the hand-sorting method at three different stations. Determination of location the sampling plot is done by purposive random sampling method. Each station has ten plots with a size of 30x30cm each. The number of eaarthworms from each plot was collected, counted, and identified. Phase II research is an electronic LKPD design that use 2 stages, namely the analysis and design stages. The results showed that three families of earthworms were found, represented by three genera. The family Megascolecidae is represented by genus Pheretima, family Glossocolecidae is represented by genus Pontoscolex, and family Lumbricidae is represented by genus Lumbricus.Key Words: Landfills; Identify; Earthworm; Hand-sorting; Electronic LKPD